White emission from polymer/quantum dot ternary nanocomposites by incomplete energy transfer - Park, JH; Kim, JY; Chin, BD; Kim, YC; Kim, JK; Park, OO (IOP PUBLISHING LTD, 2004)
White light emission was obtained from a light-emitting diode prepared from polymer/quantum dot nanocomposites consisting of poly(9,9'-dihexylfluorene-2,7-divinylene-m-phenylenevinylene-stat-p-phenylenevinylene) (PDHFPPV) and two kinds of CdSe nanoparticles with different particle size. Blue emission from the polymer, green emission from the similar to3 nm CdSe and red emission from the similar to7 nm CdSe, which is triggered by partial excitation energy transfer from the polymer, jointly contribute to white emission of the organic-inorganic hybrid device. Also, the blue-emitting matrix polymer makes the device preparation process simpler due to its high processability. By controlling the blend ratio, we could obtain a pure white colour from the hybrid device.